Significance of surfactant proteins in respiratory distress syndrome in preterm infants - İ.A. Mirzayeva; R.O. Baylarov; Y.A. Gasimova; P.A. Orujova (Сучасна педіатрія: Україна)
Respiratory diseases are considered to be widespread pathologies among preterm infants.